Plasma metabolomics in male primary and functional hypogonadism - Grande, Giuseppe; De Toni, Luca; Garolla, Andrea; Milardi, Domenico; Ferlin, Alberto (Frontiers in Endocrinology, 2023)
Metabolomics proposes to unveil the molecular machinery involved in each specific disease by the comprehensive analysis of low-molecular-weight metabolites in a biological sample. This narrative mini-review analyses previous studies applying ultra-high-performance liquid chromatography-HRMS-based metabolomics to highlight different metabolic pathways involved in male hypogonadism and testosterone replacement therapy, both in case of insulin-sensitive patients with primary hypogonadism and in case of insulin-resistent patients with functional hypogonadism. In functional hypogonadism, metabolomics revealed that different biochemical pathways are affected. In details, glycolysis is the most important biochemical process involved in these patients. Glucose metabolism is fuelled by aminoacids degradation and the gluconeogenesis is widely stimulated. Some important pathways, including glycerol, are compromised. Furthermore, mitochondrial electron transport is influenced, namely with a decrease in ATP production. On the contrary, beta-oxidation of short and medium chain fatty acids does not represent an energy source in hypogonadic patients. Both lactate and acetyl CoA are converted into ketone bodies, which increase very much. On the other side, carnosine and β-alanine are greatly reduced. These metabolic changes are associated with increased fatigue and mental confusion. After testosterone replacement therapy a complete restoration is achieved for only a part of the metabolites. It is of note that, only in patients with functional hypogonadism treated with testosterone, ketone bodies are produced at high levels, so that the symptoms sometimes reported by these patients after the beginning of the therapy (difficulty in concentrating, depressed mood, brain fog, memory impairment) might represent a specific “keto flu-like” syndrome, related to metabolic ketonic state.